Representations of Labour, Race, and Orientalism in Tale of a Certain Orient and Blackbodying - Jurdi, Erika (Université d'Ottawa | University of Ottawa, 2020)
The present research paper analyses the novels Tale of a Certain Orient by Brazilian author Milton Hatoum, and Blackbodying by Canadian author Dimitri Nasrallah, regarding their depictions of the Lebanese migratory experience in two different settings: the Amazon region in the early 20th century, and Toronto in the late 20th century. Using the frame of labour and race relations, as well as analysing the use and rejection of Orientalist stereotypes, I highlight the similarities, but mostly the differences, between various experiences of migration of people originating in the same place. While the Brazilian novel shows us the social and economic ascent of a Lebanese family in the context of early 20th century Manaus, privileged by their position in relation to their local Black and Indigenous employees, the Canadian novel brings forth the hardships and isolation of a recent immigrant fleeing war and left entirely to his own devices in a hostile new environment. I conclude that despite their regional differences, the two novels resonate with universal messages that are relevant to many people’s experiences in a globalized world shaped by migration and displacement.
Keywords: Tale of a Certain Orient; Milton Hatoum; Blackbodying; Dimitri Nasrallah; migration; race relations